KAJIAN PENERAPAN MATERIAL REUSE PADA RUBILANG HOMESTAY YOGYAKARTA - Irfanda, Saradifa Nurdiaz (Institut Seni Indonesia Yogyakarta, 2023)
A house is a building that functions as a place to live and contains facilities and infrastructure for the family. The need for houses is increasing in accordance with human growth. This highlights that the construction of houses will definitely consume a significant amount of natural materials for building construction materials. The use of material reuse can help reduce this. Several case examples were selected to identify and analyze all the challenges and factors that should be considered in designing using recycled materials. Recycling can be defined as reusing an object in a new way, without damaging the material from which it is made. Rubilang Homestay is touted as an example of a house that contributes to environmental sustainability by using reused materials for its construction and interior. The method used in this research was conducted in-depth interviews with homeowners with a direct emphasis on the use of reused materials used in Rubilang Homestay. This research aims to understand the reuse method used by Rubilang Homestay and examine the elements of reuse materials from an interior perspective. The research results are in the form of a narrative presentation of interior images and an analysis focused on reused materials.